IMPACT OF DUAL TASK TRAINING ON COGNITIVE FUNCTION, BALANCE, GAIT AND QUALITY OF LIFE IN PATIENTS WITH PARKINSON’S DISEASE - M, Monika; Physio, Dimple Choudhry; Dabla, Surekha (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background:Parkinson's disease (PD) is a progressive neurodegenerative disorder, with the main manifestations being tremors, rigidity, bradykinesia, and postural balance disorders, accompanied by a decline in cognitive function. Objective: One of the major challenges in PD is difficulty performing dual tasks, rehabilitation strategies such as dual-task training (DTT) have been proposed to simultaneously target motor and cognitive deficits. In this study, we aimed to assess the impact of dual-task training on cognitive function, balance, gait, and quality of life in patients with Parkinson’s disease. Methods: In this study, 30 patients diagnosed with idiopathic Parkinson’s disease, aged 50–70 years were randomly assigned into experimental group (n=15) receiving dual-task training and control group (n=15) receiving single-task training for 12 sessions (40 minutes each, twice weekly for 6 weeks). Outcome measures included Timed Up and Go test, step length and stride length, fluency test and PDQ-39 measured at baseline, after 3 weeks and after 6 weeks. Results: There was a statistically significant difference was found in PDQ-39 (t= -2.888, p=0. 007), Semantic Fluency test (t=3.391, p=0.002) and phonemic Fluency test (t=2.956, p=0.006) after 6 weeks between experimental and control group. Both groups showed significant improvements in balance, gait parameters after 6 weeks (p<0.05). Conclusion: Both type of training help to improve balance and gait, but dual-task training provided added gains in quality of life and cognition. Incorporating dual-task exercises into rehabilitation may therefore offer superior functional benefits by better reflecting real-world mobility demands.